Aplikasi Bakteri Endofit dan Mikoriza Terhadap Kandungan Unsur N, P dan K pada Pembibitan Tanaman Lada: Application of Endophytic Bacteria and Mycorrhizal toward N, P, and K Content of Pepper Seedling - Fahrizal Hazra; Gusmaini Gusmaini; Devi Wijayanti (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
Application of endophytic bacterial formulas and mycorrhizal expected to improve the quality of seedling in pepper. This research aims to determine the effect of endophytic bacterial formulas and mycorrhizal to the absorption of N, P, and K in Podsolik Jasinga, and the growth of pepper in seedling phase. The research method used randomized block design grouped by replication. Endophytic bacteria formulas types (B2), (B3) and without endophytic bacterial formulas (B0) as the first factor. Mycorrhiza with three levels, without mycorrhizal (M0), 10 g plant-1 (M1) and 20 g plant-1 (M2) as the second factor. The treatments tested were nine combinations and each treatment was repeated three times. This experiment obtained 27 experimental units. Each replication represented by five plants, so there were 135 plants. In general, endophytic bacteria formula of and mycorrhizal 10 g plant-1 (M1) is better to increasing the vegetative phase of pepper plants.